Konvergensi Media Periklanan dalam Konstelasi Perkembangan Teknologi Media - Setianto, Widodo Agus (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
The recent development of information technology and commuitication with the presence of new media has affected human behaviors and habit especially in media consumption patterns. Efforts should be made by the conventional mass media, as advertising media, to be in line with the new media development. This article argues that the form of advertising media in the new media environment will be convergence media advertising.